Investigations proofing the passive layer stability of stainless steels. Issue 1 (18th February 2015) - Lehmann, J.; Burkert, A.; Mietz, J.
Abstract : The presented investigations have proved the principal suitability of the KorroPad method to assess the passive layer stability of stainless steels. The electrochemical mode of action could be described in detail and limitations of the applicability have been demonstrated. The influence of different surface finishes has been investigated and verified by known methods for describing corrosion resistances. As a result, the increased corrosion susceptibility of two ground surfaces has been detected, but also the corrosion resistance of further surface finishes could be confirmed.